Antenatal corticosteroid administration in late-preterm gestations: a cost-effectiveness analysis. (17th June 2020) - Rosenbloom, Joshua I.; Lewkowitz, Adam K.; Sondgeroth, Kristina E.; Hudson, Jessica L.; Macones, George A.; Cahill, Alison G.; Tuuli, Methodius G.; Chang, Su-Hsin
Abstract: Objective: To evaluate whether administration of antenatal late-preterm betamethasone is cost-effective in the immediate neonatal period. Study design: Cost-effectiveness analysis of late-preterm betamethasone administration with a time horizon of 7.5 days was conducted using a health-system perspective. Data for neonatal outcomes, including respiratory distress syndrome (RDS), transient tachypnea of the newborn (TTN), and hypoglycemia, were from the Antenatal Betamethasone for Women at Risk for Late-Preterm Delivery trial. Cost data were derived from the Healthcare Cost and Utilization Project from the Agency for Health Care Research and Quality, and utilities of neonatal outcomes were from the literature. Outcomes were total costs in 2017 United States dollars and quality-adjusted life years (QALYs) for each individual infant as well as for a theoretical cohort of the 270 000 late-preterm infants born in 2015 in the USA. Results: For an individual patient, compared to withholding betamethasone, administering betamethasone incurred a higher total cost ($6592 versus $6265) and marginally lower QALYs (0.02002 QALYS versus 0.02006 QALYs) within the studied time horizon. For the theoretical cohort of 270 000 patients, administration of betamethasone was $88 million more expensive ($1780 million versus $1692 million) with lower QALYs (5402 QALYs versus 5416 QALYs), compared to withholding betamethasone. For administration of betamethasone to be cost-effective, the rate of hypoglycemia, RDS, or TTN among late-preterm infants receiving betamethasone would need to be less than 20.0, 4.5, and 2.4%, respectively. Conclusion: Administration of betamethasone in the late-preterm period is likely not cost-effective in the short-term.